2011
DOI: 10.1109/tthz.2011.2164654
|View full text |Cite
|
Sign up to set email alerts
|

A Room Temperature Bolometer for Terahertz Coherent and Incoherent Detection

Abstract: Index Terms-Bolometer, mixer, terahertz (THz), submillimeter, YBCO. room temperature detector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Previously we reported that the bolometer responsivity scales inversely with the device lateral dimensions (the width times the length), which is in concurs with the bolometer cooling into the substrate via the phonon exchange [4]. There, we predicted a great improvement of the sensitivity when the bolometer size becomes sub micrometer.…”
Section: Introductionsupporting
confidence: 83%
“…Previously we reported that the bolometer responsivity scales inversely with the device lateral dimensions (the width times the length), which is in concurs with the bolometer cooling into the substrate via the phonon exchange [4]. There, we predicted a great improvement of the sensitivity when the bolometer size becomes sub micrometer.…”
Section: Introductionsupporting
confidence: 83%
“…Room temperature, portable focal plane arrays (FPAs) are in high demand for terahertz (THz) imaging systems and applications in recent years [1][2][3][4]. As compared to conventional Schottky diodes, Sb-based HBD devices exhibit higher zero-bias curvature coefficient (γ), intrinsically higher responsivity and lower noise equivalent power (NEP) level, making them suitable for THz detection and imaging at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…1 (b)) with number of turns N =3, arm width w=12 ȝm and arm gap g=12 ȝm. According to antenna theory, the embedding impedance at the feed point of the FDA is proportional to N by [4],…”
Section: Introductionmentioning
confidence: 99%
“…Their most important advantage is the wide detection range, from THz to x rays, although they suffer from a slow response time of the order of milliseconds at liquid helium temperature [6]. Recently, antenna coupled superconducting bolometers have been reported to operate at higher temperatures [7,8]. Nevertheless, their detection bandwidth is limited to the bandwidth of the antenna.…”
Section: Introductionmentioning
confidence: 99%